What is the Outcome of Platelet-Rich Fibrin Therapy Compared to Connective Tissue Grafting When Treating Gingival Recession? - Kelsea Collins; Quatesha Smith; Ashley Christman, RDH, BS (Elsevier, 2024)
OBJECTIVES: To educate and inform patients about Research on PRF therapy and Connective Tissue Grafting, gingival recession treatment, and Platelet-Rich Fibrin therapy so they can make informed decisions about their needed gingival procedures. METHODS: For this literature review, the question was formulated to uncover new or less-known data regarding the restoration of gingival recession. Specifically, the question focused on comparing the outcomes of plateletrich fibrin (PRF) therapy to connective tissue grafting in the treatment of gingival recession. To locate relevant articles, the following MeSH terms were used: "gingiva, gingiva rejuvenation, gum graft, connective tissue graft, and PRF gingiva." To ensure the specifics of the search, meta-analyses, literature reviews, systematic reviews, and articles published before 2018 were excluded. RESULTS: Using PRF therapy is appealing because it comes from the patient's own body and might cause fewer problems. The studies reviewed demonstrate a spectrum of outcomes, with some suggesting equivalence between PRF and connective tissue grafting, while others emphasize that connective tissue grafting is still a very effective option. One is not simply seen as better than the other, but a preference for the patients. CONCLUSIONS: Gingival recession management is a complex issue, with both connective tissue grafting and platelet-rich fibrin (PRF) therapy being treatment options. PRF therapy, which uses growth factors, is effective but depends on gingiva receding, patient-specific factors, and treatment methods. IMPLICATIONS: Informing patients about platelet- rich fibrin therapy in comparison to connective gingival tissue grafting gives the patient the ability to decide what they believe is best of care.